Pengaruh Profitabilitas, Likuiditas Dan Leverage Terhadap Keterlambatan Publikasi Laporan Keuangan Interim Perusahaan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2022 - Afif Luthfi; Tri Joko Prasetyo (Journal on Education, 2024)
Financial statements are essential documents prepared based on certain criteria that provide information about a company's financial performance, changes in equity, cash flows, and assets. These reports serve as tools to communicate the company's status to external stakeholders. High-quality financial statements are crucial as they offer relevant, reliable, comparable, and easily understandable information for internal and external decision-makers. However, delays in submitting financial statements can undermine the reliability and transparency of the information provided to investors and other stakeholders. The Financial Services Authority (OJK) is responsible for overseeing the financial reporting of companies listed on the Indonesia Stock Exchange (BEI) and ensuring compliance with applicable regulations. Although regulations have been enacted to ensure timely financial reporting, many companies still fail to fulfill this obligation. Companies that do not submit audited financial statements may face sanctions from the BEI in the form of fines. Therefore, companies need to ensure timely submission of financial statements to maintain trust and confidence among stakeholders.